A rare case report of waldenström macroglobulinemia converted to serum low IgM - Xiang, Yuan; Fang, Shi-Qiang; Liu, Yi-Wen; Wang, Hui; Lu, Zhong-Xin (Frontiers in Genetics, 2023)
Waldenström Macroglobulinemia(WM) is a rare chronic lymphoproliferative disease, accounting for less than 2% of hematological malignancies. It is characterized by plasma cytoid lymphocyte infiltration in bone marrow and abnormal increase of monoclonal IgM in peripheral blood. Only 5% to 10% of cases of WM secrete monoclonal IgG and IgA components or do not secrete monoclonal long immunoglobulin. This case is the first to report of serum protein recombination from lgM and KAP band mutation to abnormal lgG and KAP band after 6 years of treatment in a male patient with WM.